2014
DOI: 10.1007/s11356-014-2544-1
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality (IAQ) assessment in a multistorey shopping mall by high-spatial-resolution monitoring of volatile organic compounds (VOC)

Abstract: In order to assess indoor air quality (IAQ), two 1-week monitoring campaigns of volatile organic compounds (VOC) were performed in different areas of a multistorey shopping mall. High-spatial-resolution monitoring was conducted at 32 indoor sites located in two storehouses and in different departments of a supermarket. At the same time, VOC concentrations were monitored in the mall and parking lot area as well as outdoors. VOC were sampled at 48-h periods using diffusive samplers suitable for thermal desorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The difference in pollutants levels between hot spring hotel rooms and previously reported rooms was due to the decoration and furniture materials used in the room, and high toluene levels were found in Hotel 1 in southern China due to the usage of poor quality carpet fitted in the room [12,15,33]. In general, BTEX could be found in new and refurbished buildings during the decoration because some BTEX were commonly used as solvents for carpet adhesive [2,12,14]. High concentrations of BTEX could be attributed to the usage of plywood furniture, wardrobes and carpets fitted in the hotel rooms [12].…”
Section: Voc Levelsmentioning
confidence: 96%
See 1 more Smart Citation
“…The difference in pollutants levels between hot spring hotel rooms and previously reported rooms was due to the decoration and furniture materials used in the room, and high toluene levels were found in Hotel 1 in southern China due to the usage of poor quality carpet fitted in the room [12,15,33]. In general, BTEX could be found in new and refurbished buildings during the decoration because some BTEX were commonly used as solvents for carpet adhesive [2,12,14]. High concentrations of BTEX could be attributed to the usage of plywood furniture, wardrobes and carpets fitted in the hotel rooms [12].…”
Section: Voc Levelsmentioning
confidence: 96%
“…Except for outdoor air travelling inside, the most common source of indoor pollutants, like CO, CO2, PM and VOCs, include building materials (e.g., floor and wall coverings, carpet), combustion processes (e.g., smoking, cooking, home heating), consumer products (e.g., cleaners, air fresheners, mothballs), human activity (e.g., moving, and house work) and some other sources [1,[9][10][11][12]. Benzene, toluene, ethyl-benzene, xylene (BTEX), as the main compounds of VOCs in indoor air with a concentration range from 1 to several hundredµ g·m −3 , are usually emitted from building materials and furniture, or are usually used as solvents during wood processing, printing and other daily usage [2,[12][13][14][15]. Since BTEX are one typical kind of harmful VOCs, the health risks and source analysis of BTEX in indoor air have attracted extensive attention [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…A study by the Lawrence Berkeley National Laboratory concludes that increasing ventilation to improve IAQ may not be effective, nor is it economical [42]. In this monitoring campaign, we observed higher TVOC concentrations in mornings and evenings, possibly due to reduced ventilation operations at night [43,44] or the cleaning activities that occurred before stores opened and after they were closed [21]. It was unfortunate that we could not measure ventilation rates, which restricted us from further studying the association between ventilation and in-store TVOC.…”
Section: Discussionmentioning
confidence: 99%
“…Data are insufficient regarding VOC levels and their influencing factors in stores, setting a barrier to adequate controls and regulations [14]. A few case studies provide detailed analyses of VOC variability in individual large shopping malls [21,22], but no study has been specifically designed to examine how indoor VOC levels vary between stores and spatially within stores. This study was designed to fill this knowledge gap by measuring concentrations of total VOCs (TVOC) in different categories of stores.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of benzene in a multistory shopping mall in the suburbs of Bari, Italy was found to be 0.10–5.28 μg/m 3 and 0.60–9.14 μg/m 3 in the first and second sampling campaign, respectively, carried out at a gap of 10 months. The average Indoor/Outdoor (I/O) ratio of benzene in supermarket and storehouses were 0.8 and 0.9 respectively which according to the authors indicated that the benzene in the indoor environment is due to the outdoor benzene (Amodio et al., 2014). The level of benzene found in the gasoline shops at the City of Belo Horizonte, Brazil was 39.81 ± 63.30 μg/m 3 (Helvécio C. Menezes et al., 2009).…”
Section: Indoor Benzene Concentrationmentioning
confidence: 99%